2019
DOI: 10.1002/ep.13252
|View full text |Cite
|
Sign up to set email alerts
|

Facile salt‐free process for cotton fabric dyeing: Pad‐irradiate‐pad‐steam process using 3‐chloro‐2‐hydroxypropyl trimethyl ammonium chloride

Abstract: Severe effluent pollution has set new requirements for eliminating the use of salts during the reactive dyeing of cotton. In this study, 3‐chloro‐2‐hydroxypropyltrimethylammonium chloride was used as an etherifying agent via a pad‐irradiate‐pad‐steam process with a reactive dye to cationize cotton. The fabric underwent a microwave‐assisted pad‐irradiate process, and the cationic fabric was dyed salt‐free using a reactive dye in a pad‐steam process. The influence of etherifying conditions on the nitrogen conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Compared to RC, the initial decomposition temperature of MdC-Op is decreased as can be see from the DTG curves of MdC-Op and RC in Fig. 2e, which might be due to that the thermal decomposition capacity of CHPTAC is lower than that of cotton (Yu et al 2019). The half life temperature and weightlessness rate of MdC-Op is increased slightly demonstrating the improved thermal stability of MdC-Op (Yao et al 2021).…”
Section: Structural Characterization Of Mdc-opmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared to RC, the initial decomposition temperature of MdC-Op is decreased as can be see from the DTG curves of MdC-Op and RC in Fig. 2e, which might be due to that the thermal decomposition capacity of CHPTAC is lower than that of cotton (Yu et al 2019). The half life temperature and weightlessness rate of MdC-Op is increased slightly demonstrating the improved thermal stability of MdC-Op (Yao et al 2021).…”
Section: Structural Characterization Of Mdc-opmentioning
confidence: 86%
“…Small-molecule modifiers can modify the fibers uniformly because of their good solubility, which could solve the uneven dyeing of the cationic fibers (Park et al 2010). Among various chemical reagents, 3-chloro-2-hydroxypropyl trimethyl ammonium chloride (CHPTAC) is considered a promising cationic modifier (Yu et al 2019). Wang et al (2020b) prepared a hybrid ink composed of CHPTAC and reactive dye to print plain-woven cotton.…”
Section: Introductionmentioning
confidence: 99%
“…After determining the preliminary range of cationizing variables in the pad‐irradiate process, the CHPTMAC concentration, the microwave irradiation power, the treatment time, and the molar ratio of sodium hydroxide‐to‐CHPTMAC were defined as the four experimental variables for CCD . The coded and actual values of the experimental design factors are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Microwave irradiation has also great potential for use in the textile industry for replacing conventional heating methods as it is more uniform and faster than conventional conduction or convection heating methods . Based on our preliminary studies, pad‐irradiate‐pad‐steam (PIPS) is a feasible route to simultaneously cationize and dye cotton fabric compared to the conventional PDPS process, which is a new and green dyeing process that conforms with the modern needs for social development because it protects the environment by eliminating the use of salt, which is a central motivation to study the dyeing conditions with a reactive dye in the PIPS process. However, the key task of PIPS process is to determine the optimum etherifying condition.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al 16 pioneered a novel continuous dyeing route, who reported on the introduction to the cationisation of cotton fabrics in brief, the pad‐irradiate‐pad‐steam (PIPS) process, and the conditions which influenced the nitrogen content and grafting efficiency of cotton fibre. In this article, the influence of cationising conditions in the pad‐irradiate sub‐process (eg, CHPTMAC concentration, microwave irradiation power, treatment time and the mole ratio of sodium hydroxide to CHPTMAC) on the reactive dyeing process and the properties of the resulting dyed cationic fabric were studied.…”
Section: Introductionmentioning
confidence: 99%